Gulag memories the rediscovery and commemoration of Russia's repressive past - Bogumił, Zuzanna (Berghahn, 2018)
Though the institution of the Gulag was nominally closed over half a decade ago, it lives on as an often hotly contested site of memory in the post-socialist era. This ethnographic study takes a holistic, comprehensive approach to understanding memories of the Gulag, and particularly the language of commemoration that surrounds it in present-day Russian society. It focuses on four regions of particular historical significance-the Solovetsky Islands, the Komi Republic, the Perm region, and Kolyma-to carefully explore how memories become a social phenomenon, how objects become heritage, and how the human need to create places of memory has preserved the Gulag in specific ways today
"Polish-language edition, ©2012 Universitas, originally published by Universitas as Pamięć Gułagu."
Keywords: Geschichte; Politische Verfolgung -- Motiv; Arbeitslager; Straflager -- Motiv; Konzentrationslager; Kollektives Gedächtnis; Sowjetunion; Russland; Concentration camps / Soviet Union; Political prisoners / Soviet Union; Memorialization / Russia (Federation); Concentration camps; Memorialization; Political prisoners; Russia (Federation); Soviet Union